Evolution of Russian foreign policy towards the Baltic States at the present Stage - S. S. Boykov (Проблемы постсоветского пространства, 2020)
The article gives an analysis of Russia’s foreign policy in relation to the Baltic States from 1990 to 2019. The author identifies four main stages of its evolution. It is concluded that the main problems of the Russian-Baltic dialogue are discrimination of the Russian-speaking minority, issues of historical memory, a decrease of the Russian transit and security. The relations between Russia and the Baltic states has become conflict almost after dissolution of the USSR. However, in 1990-2000-ies, Russia still tried to formulate a positive agenda for the relations with the Baltics. The main motive of its strategy was to build trust and political relations on the basis of economic cooperation and civil society. Since 1990-s Russia has been developing cross-border cooperation programs. Since late 2000-s Russia has been also developing cross-border programs with the EU. However, Russia’s hopes were not justified. Its relations with Latvia, Estonia and Lithuania have worsened since 2014 after the Ukrainian conflict. Prospects for their improvement are still unclear. The author comes to the conclusion that Russia is “tired” from the Baltic States. Despite the fact that Russia has been systematically transforming its foreign policy after the dissolution of the USSR, it has not fully achieved its goals. There is still discrimination of the Russian minority. Russia and the Baltics have not come to a single interpretation of the Second World War history. Political contradictions prevail over economic ties. Despite the growing estrangement between Russia and the Baltic States, Russia keeps developing them concentrating on trans-border and civil society cooperation. Such relations are non-political and they are focused on solving specific problems.